FORMATION OF LOGISTIC STRATEGY OF ECONOMIC SECURITY SYSTEM OF TRANSPORT COMPANIES WITH USE OF ECONOMIC-MATHEMATICAL MODELING APPARATUS - BOHDANETS, Taras (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of this scientific research is to conduct a comprehensive and in-depth study of the logistics strategy within the framework of the economic security system at agro-industrial enterprises, using modern tools of economic and mathematical modeling. In today’s dynamic and often unpredictable economic environment, ensuring stability and resilience in the agricultural sector requires the development of robust strategic frameworks that can respond effectively to emerging challenges. Therefore, this work emphasizes the relevance and necessity of forming adaptive and analytically grounded logistics strategies to safeguard the economic interests of agro-industrial enterprises. To address the scientific challenges outlined in this study, a combination of methodological approaches was employed. These include the structural method, which allows for the breakdown and analysis of the logistics strategy components; comparative analysis of empirical data to highlight best practices and identify gaps; abstract-logical generalization to synthesize theoretical insights; and, crucially, economic and mathematical modeling to provide a quantitative basis for decision-making. Together, these methods support a comprehensive evaluation and the formulation of practical recommendations. The core contribution of this study lies in the development of a novel economic and mathematical model for forming the logistics strategy of agro-industrial enterprises, viewed through the lens of economic security. Unlike pre-existing models, the proposed approach allows for the construction of implementation plans that are not only tailored to the current informational state of the enterprise but are also aligned with specific decision-making criteria necessary for resolving targeted operational problems. The model incorporates principles of optimization under resource constraints, enabling enterprises to make informed and efficient choices in resource allocation. Overall, the findings presented in this work are expected to provide actionable insights and a methodological framework that domestic agro-industrial enterprises can adopt. By applying the algorithm for forming a logistics strategy based on resource limitation principles, enterprises can strengthen their economic security and enhance their strategic planning capacity in a competitive and rapidly evolving market environment.